Inhabiting Time: Towards A Heterophony of Temporalities and Traditions - Bhagwati, Sandeep (Intersections, 2021)
In this text, the author argues that heterophony is not just the unkempt shadow of polyphony. On the contrary: its vaguely defined “otherness” opens up new potentials for musicking—especially if we ask how we could conceive of music other than through synchrony, the principle that underpins central musical features such as consonance, harmony, beat, and groove. The world around us is not usually wrought from synchrony. Rather, the vast range of timescales from particle physics to cosmology that traverse us do not rely on synchronized polyphony to deeply impact future life on this planet. Therefore, might musicking in temporal heterophony offer us new ways of being and of listening—a renewed sensibility for the temporalities we inhabit and impact?